CLINICAL AND SOCIODEMOGRAPHIC FACTORS ASSOCIATED WITH QUALITY OF LIFE IN EPILEPSY PATIENTS AT DORIS SYLVANUS HOSPITAL PALANGKA RAYA - Ariqah Ghaniyah Lembah; Ranintha Br. Surbakti; Ravenalla Abdurrahman Al Hakim Sampurna Putra Solihin; Farah Fauziyah Radhiyatulqalbi Ahmad; Nuch Sabunga (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Epilepsy is a chronic neurological disorder that affects patients' physical, psychological, and social aspects, influencing their quality of life (QoL). Identifying clinical and sociodemographic factors related to QoL is essential for comprehensive management. Objective: To analyze the relationship between clinical and sociodemographic factors and the quality of life of epilepsy patients at the Neurology Polyclinic of RSUD dr. Doris Sylvanus Palangka Raya. Methods: This analytical observational study with a cross-sectional design involved 53 respondents selected through consecutive sampling. Data were collected using the QOLIE-31 to assess QoL, the MARS-5 to assess medication adherence, the MSPSS to assess social support, and a validated knowledge questionnaire. Relationships between variables were analyzed using the Spearman correlation test with a significance level of p < 0.05. Results: Most respondents were adults aged 19-45 years (83.0%), male (52.8%), and had secondary education. The mean QOLIE-31 score was 52.24 (SD 20.02), indicating moderate QoL. Significant correlations were found between seizure frequency (r = -0.506; p < 0.001), comorbidity (r = -0.368; p = 0.007), medication adherence (r = 0.483; p < 0.001), social support (r = 0.396; p = 0.004), and knowledge level (r = 0.587; p < 0.001) with QoL. Age at diagnosis (p = 0.119) and epilepsy duration (p = 0.397) were not significantly related. Conclusion: Quality of life in epilepsy patients is significantly associated with seizure frequency, comorbidity, medication adherence, social support, and knowledge level. Improving adherence and psychosocial support can enhance patients' overall well-being.